The importance of academic advising and its intervention action in advising students who are near the border of passing or failing an engineering program - Omar J.B. (2023)
Perceived as a relatively tough field, some students cannot complete their engineering program successfully. Systematic and correct academic advising is one factor that can contribute to students successfully graduated from their studies in an engineering program, especially for students who are near the border of passing or failing the program. 2010 IEEE.